Tmbim4 protects against triclocarban-induced embryonic toxicity in zebrafish by regulating autophagy and apoptosis. (15th May 2021) - Hu, Zhiyong; He, Liting; Wei, Jiajing; Su, Yufang; Wang, Wei; Fan, Zunpan; Xu, Jia; Zhang, Yuan; Wang, Yongfeng; Peng, Meilin; Zhao, Kai; Zhang, Huiping; et al.
Abstract: Triclocarban (TCC), an antibacterial agent widely used in personal care products, can affect embryonic development. However, the specific molecular mechanism of TCC-induced embryonic developmental damage remains unclear. In this study, TCC exposure was found to increase the expression of tmbim4 gene in zebrafish embryos. The tmbim4 mutant embryos are more susceptible to TCC exposure than wild-type (WT) embryos, with tmbim4 overexpression reducing TCC-induced embryonic death in the former. Exposure of tmbim4 mutant larvae to 400 μg/L TCC substantially increased apoptosis in the hindbrain and eyes. RNA-sequencing of WT and tmbim4 mutant larvae indicated that knockout of the tmbim4 gene in zebrafish affects the autophagy pathway. Abnormalities in autophagy can increase apoptosis and TCC exposure caused abnormal accumulation of autophagosomes in the hindbrain of tmbim4 mutant zebrafish embryos. Pretreatment of TCC-exposed tmbim4 mutant zebrafish embryos with autophagosome formation inhibitors, substantially reduced the mortality of embryos and apoptosis levels. These results indicate that defects in the tmbim4 gene can reduce zebrafish embryo resistance to TCC. Additionally, apoptosis induced by abnormal accumulation of autophagosomes is involved in this process. Graphical abstract: Image 1 Highlights: Triclocarban induces upregulation of tmbim4 gene expression in zebrafish embryos. tmbim4 -deficient zebrafish embryos are susceptible to triclocarban exposure Triclocarban causes increased apoptosis in hindbrain and eyes leading to death in tmbim4 -deficient zebrafish embryos. Abnormal accumulation of autophagosomes leading to death of triclocarban exposed tmbim4 -deficient zebrafish embryos. Abstract : Apoptosis and autophagy are involved in the process of tmbim4 mutant zebrafish that are less resistant to TCC.